SNR Based DSDV Routing Protocol for MANET - Mohd Fairuz, Muhamad Fadzil (2012)
A wireless mobile ad-hoc (MANET) network is a dynamic formation of wireless nodes to perform a temporary network without center administration node. The wireless node which is also known as mobile platform are free to move randomly within its network coverage. The MANET is an autonomous system which operates in isolation (local area network only) or may have gateways to an interface with a fixed network. One of the main parts of MANET is its routing protocol in network layer. The protocol has to decide which path that needs to be taken by packets to ensure the packet transfer from sender to receiver. The algorithms that calculate these paths are referred as routing algorithms (Kurose, 2009) Due to unpredictable behavior of the wireless medium in MANETs environment, the standard routing protocol based on hop count suffers due to the noise that collected at receiving nodes (Douglas, 2003). In this project the Signal-to-Noise (SNR) based routing protocol has been adapted into the standard Destination Sequenced Distance Vector (DSDV) routing algorithm by developing an algorithm to calculate the cumulative average SNR from source to destination and apply the algorithm in the DSDV routing protocol. The expected result is SNR based DSDV routing protocol and the outcome would be comparisons of performance metrics between standard DSDV for the throughput, end-to-end delay and packet delivery ratio versus transmission rate and node numbers.